EFFECT OF MATERNAL VITAMIN D SUPPLEMENTATION DURING LACTATION EFFECT ON INFANTS' PROPENSITY TO INFECTION : AN EVIDENCE-BASED CASE REPORT - Raphael Kosasih; Diana Sunardi (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2021)
Abstract Introduction: Vitamin D deficiency has become more prevalent around the world along with a sedentary lifestyle and limited exposure to sunlight. Deficiencies of vitamin D in lactating mothers could cause deficiencies in their infants and vitamin D deficient infants are at higher risk of having infectious diseases. Supplementation of Vitamin D to lactating mothers may benefit both mothers and infants to reduce infection morbidity. Methods: Relevant literature research was conducted in PubMed, Cochrane, and SciELO using relevant keywords and advanced search methods. Relevant literature was then screened for duplication, relevance, and eligibility. Results: A randomized-controlled trial was selected. The study showed that supplementation of 3000µg oral vitamin D3 to lactating mothers significantly raise their infants' serum vitamin D (p<0.01) and reduce infection morbidity (p<0.01) Conclusions: Oral supplementation of vitamin D3 could be given to lactating mothers to improve their infants' serum vitamin D and reduce infection morbidity. Keywords: vitamin D, lactation, infants' infection